Distribution, Characteristics, and Ecological Risk Assessment of Microplastics and Heavy Metals in Surface Water at Hoa Binh Reservoir - Thi My, Nguyen; Thi Oanh, Doan; Thi Anh Nguyet, Nguyen; Phuong Thao, Pham; Le Anh, Pham; Thuy Duong, Nguyen; Van Huong, Nguyen; Hue Nhu, Nguyen; Anh Tu, Tran; Thi Diem My, Ngo; Thi Phuong Quynh, Le; Thi Minh Hanh, Pham; et al. (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 2DO - 10.25073/2588-1094/vnuees.5377, 2025)
The co-presence of microplastics (MPs) and heavy metals (HM) in aquatic ecosystems may increase ecological risks due to adsorption, transport, and accumulation mechanisms. This study investigated the distribution of microplastics and heavy metals in water samples collected from Hoa Binh reservoir at two times: July (rainy season) and November (dry season) of 2024. Microplastic concentration, shape, size, color, and seven heavy metals (Cr, Mn, Fe, Ni, Cu, Zn, and Pb) were characterized. Microplastics were detected at all sampling sites, with mean abundances ranging from 6.20 ± 0.17 to 22.99 ± 2.43 MPs/m³. Fibrous particles predominated (84.65 ± 12.38%), and white was the most common color. Polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET) were the dominant polymers. Heavy metal concentrations varied seasonally, with higher levels recorded during the dry season. Pearson correlation analysis revealed significant positive relationships between microplastics and certain heavy metals, particularly Pb (r = 0.88), suggesting a potential shared source or co-accumulation process. The potential ecological risk assessment (PERI) results recorded low levels of heavy metals in both seasons. Meanwhile, the PERI values ​​of microplastics were at medium and high levels in the dry season and low levels in the rainy season. These findings highlight the importance of integrating the monitoring of microplastics and heavy metals to minimize ecological and human health risks in freshwater reservoirs. Keywords:   The co-presence of microplastics (MPs) and heavy metals (HM) in aquatic ecosystems may increase ecological risks due to adsorption, transport, and accumulation mechanisms. This study investigated the distribution of microplastics and heavy metals in water samples collected from Hoa Binh reservoir at two times: July (rainy season) and November (dry season) of 2024. Microplastic concentration, shape, size, color, and seven heavy metals (Cr, Mn, Fe, Ni, Cu, Zn, and Pb) were characterized. Microplastics were detected at all sampling sites, with mean abundances ranging from 6.20 ± 0.17 to 22.99 ± 2.43 MPs/m³. Fibrous particles predominated (84.65 ± 12.38%), and white was the most common color. Polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET) were the dominant polymers. Heavy metal concentrations varied seasonally, with higher levels recorded during the dry season. Pearson correlation analysis revealed significant positive relationships between microplastics and certain heavy metals, particularly Pb (r = 0.88), suggesting a potential shared source or co-accumulation process. The potential ecological risk assessment (PERI) results recorded low levels of heavy metals in both seasons. Meanwhile, the PERI values ​​of microplastics were at medium and high levels in the dry season and low levels in the rainy season. These findings highlight the importance of integrating the monitoring of microplastics and heavy metals to minimize ecological and human health risks in freshwater reservoirs.